Slow-speed compared with fast-speed eccentric muscle actions are detrimental to jump performance in elite soccer players in-season - Houtmeyers, K. C.; Robberechts, P.; Jaspers, A.; McLaren, S. J.; Brink, M. S.; Vanrenterghem, J.; Davis, J. J.; Helsen, W. F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine the effect of fast- versus slow-speed eccentric-muscle-action resistance training on lower-body strength, vertical jump height, sprint speed, and change-of-direction performance in elite soccer players during a competitive season. 'Methods: Twenty-two elite soccer players, from a single team, were randomly assigned to groups that undertook either 1- (fast speed) or 4-second (slow speed) eccentric resistance training during the in-season period. A 5-week program was conducted during an elite top-division European League soccer season. Performance measures including predicted 1-repetition-maximum back squat, countermovement jump, 20-m sprint, and change of direction were tested before and after the intervention period. Total match and training running distance and muscle soreness were also recorded during each week of the intervention. Results: An analysis of covariance showed significant group effects (P = .01) for countermovement jump with a greater jump height in the 1-second fast-speed group postintervention (95% CI, 1.1-6.9 cm). Despite an overall increase in 1-repetition maximum pretraining to posttraining (95% CI, 10.0-15.3 kg, effect size 0.69), there were no significant differences (P > .05) between groups after the intervention. Similarly, there were no differences between groups for change of direction, 20-m sprint, or muscle soreness. Conclusion: Faster eccentric muscle actions may be superior for increasing movements in elite soccer players in-season.